2004
DOI: 10.4065/79.4.504
|View full text |Cite
|
Sign up to set email alerts
|

Management of Immune Thrombocytopenic Purpura in Adults

Abstract: Primary immune thrombocytopenic purpura (ITP), also referred to as idiopathic thrombocytopenic purpura, is an organ-specific autoimmune disorder in which antibody-coated or immune complex-coated platelets are destroyed prematurely by the reticuloendothelial system, resulting in peripheral blood thrombocytopenia. The disease is heterogeneous with regard to its severity and clinical course and is unpredictable in its response to therapy. Although the basic underlying pathophysiology of ITP has been known for mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
185
1
11

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(198 citation statements)
references
References 152 publications
1
185
1
11
Order By: Relevance
“…[1][2][3][4][5] ITP signs and symptoms vary widely. Some patients have no symptoms or minimal bruising, whereas others experience severe bleeding.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] ITP signs and symptoms vary widely. Some patients have no symptoms or minimal bruising, whereas others experience severe bleeding.…”
Section: Introductionmentioning
confidence: 99%
“…The possible pathogenesis of thrombocytopenia in dengue fever are enhanced peripheral destruction of antibody coated platelets, acute bone marrow suppression leading to a megakaryocytic condition and increased destruction of platelets by the reticuloendothelial system which helps to plan for the future research in severe complications of dengue fever. 2,3 Our study demonstrated that the all three groups are similar in the increasing platelet count in dengue fever with thrombocytopenia patients (Figure 2). The rise in mean platelet count remained similar in all the groups.…”
Section: Discussionmentioning
confidence: 77%
“…Other mechanisms are acute bone marrow suppression leading to a megakaryocytic condition and increased destruction of platelets by the reticuloendothelial system. 2,3 Dengue fever causes thrombocytopenia commonly which often leads to life threatening complications like dengue hemorrhagic fever (DHF) and dengue shock syndrome (DSS). Both are fatal complications leading to hemorrhagic diathesis and circulatory collapse.…”
Section: Introductionmentioning
confidence: 99%
“…It is characterised by a transient or persistent decrease in platelets and an increase in the risk of bleeding [1][2][3][4][5]. The estimated incidence of ITP is 100 cases per 1 million persons per year, with approximately 50% of these cases occurring in children [2,6].…”
Section: Introductionmentioning
confidence: 99%
“…In adults, the incidence is higher in women than in men [2], whereas the reverse is true in children, where ITP predominates in young male [7]. Clinical presentation varies from asymptomatic or mild symptoms (bruising and petechiae) to mucocutaneous bleeding that can become severe [5,8].…”
Section: Introductionmentioning
confidence: 99%